A comparison of two models of creativity: Divergent thinking and creative expert performance. (February 2016) - An, Donggun; Song, Youngmyung; Carr, Martha
Abstract: This study examined whether and how general intelligence, domain knowledge, motivation, creative behavior, and creative personality predict two models of creativity. Two models of creativity were tested on a sample of 143 college students. Structural equation modeling was used to test the models that included the measures of general intelligence, domain knowledge, motivation, creative behavior, and creative personality as predictors of either creativity as divergent thinking or creativity as expert performance. Results were very different for the two models of creativity. General intelligence and creative personality predicted creativity as divergent thinking. However, general intelligence, domain knowledge, and motivation predicted creativity as creative expert performance. In both models, motivation predicted creative behavior. Highlights: Two models of creativity were tested using structural equation modeling. Intelligence and personality predicted divergent thinking. Intelligence, domain knowledge, and motivation predicted expert performance.